The anticipatory corpse medicine, power, and the care of the dying - Bishop, Jeffrey Paul (Notre Dame studies in medical ethics., 2011)
"In this original and compelling book, Jeffrey P. Bishop, a philosopher, ethicist, and physician, argues that something has gone sadly amiss in the care of the dying by contemporary medicine and in our social and political views of death, as shaped by our scientific successes and ongoing debates about euthanasia and the "right to die"--or to live._The Anticipatory Corpse: Medicine, Power, and the Care of the Dying, informed by Foucault's genealogy of medicine and power as well as by a thorough grasp of current medical practices and medical ethics, argues that a view of people as machines in motion--people as, in effect, temporarily animated corpses with interchangeable parts--has become epistemologically normative for medicine. The dead body is subtly anticipated in our practices of exercising control over the suffering person, whether through technological mastery in the intensive care unit or through the impersonal, quasi-scientific assessments of psychological and spiritual "medicine."The result is a kind of nihilistic attitude toward the dying, and troubling contradictions and absurdities in our practices. Wide-ranging in its examples, from organ donation rules in the United States, to ICU medicine, to_"spiritual surveys," to presidential bioethics commissions attempting to define death, and to high-profile cases such as Terri Schiavo's, The Anticipatory Corpse explores the historical, political, and philosophical underpinnings of our care of the dying and, finally, the possibilities of change. A ground-breaking work in bioethics, this book will provoke thought and argument for all those engaged in medicine, philosophy, theology, and health policy."With extraordinary philosophical sophistication as well as knowledge of modern medicine, Bishop argues that the body that shapes the work of modern medicine is a dead body. He defends this claim decisively with with urgency. I know of no book that is at once more challenging and informative as The Anticipatory Corpse. To say this book is the most important one written in the philosophy of medicine in the last twenty-five years would not do it justice. This book is destined to change the way we think and, hopefully, practice medicine." -Stanley Hauerwas, Duke Divinity School "Jeffrey Bishop carefully builds a detailed, scholarly case that medicine is shaped by its attitudes toward death. Clinicians, ethicists, medical educators, policy makers, and administrators need to understand the fraught relationship between clinical practices and death, and The Anticipatory Corpse is an essential text. Bishop's use of the writings of Michel Foucault is especially provocative and significant. This book is the closest we have to a genealogy of death." Arthur W. Frank, University of Calgary "Jeffrey Bishop has produced a masterful study of how the living body has been placed within medicine's metaphysics of efficient causality and within its commitment to a totalizing control of life and death, which control has only been strengthened by medicine's taking on the mantle of a bio-psycho-socio-spiritual model. This volume's treatment of medicine's care of the dying will surely be recognized as a cardinal text in the philosophy of medicine." H. Tristram Engelhardt, Jr., Rice University, Baylor College of Medicine"--Provided by publisher.